Optimasi formula enkapsulasi ekstrak propolis Trigona menggunakan maltodekstrin-gum biji selasih dengan teknik spray drying - Bendi Sabela; Dede Robiatul Adawiyah; Nur Wulandari (AGROINTEK, 2025)
Propolis has the potential to be widely used in the food industry due to its biological activities that are beneficial for human health, including as an antioxidant. The objectives of this research were to produce encapsulated propolis extract powders (EPEP) in optimum formula using a combination of coating materials (maltodextrin and basil seed gum (BSG)) by spray drying technique, and determining the physicochemical characteristics of the optimum EPEP. The independent variables used for optimization were 1–10 g of liquid propolis extract (factor 1) and 0–0.5 g of dried crude BSG (factor 2). Maltodextrin (10 g) and aquades (100 ml) were set as fixed variables. The optimization used response surface methodology (RSM). The responses studied were moisture content, solubility, and total phenolic content (TPC). Based on the overall response, the optimum formula resulting from RSM was 10 g of liquid propolis extract and 0.5 g of dried crude BSG with a desirability value of 0.734. The optimum EPEP had a moisture content of 3.82%, solubility of 96.13%, and TPC of 901.84 mg gallic acid equivalent (GAE)/kg sample, water activity value of 0.41, hygroscopicity value of 16.82%, and fat content of 4.61%. The results of the antioxidant activity of the optimum product by 2.2-diphenyl-1-picrylhydrazyl (DPPH) assay had an inhibition percentage of 17.61% at a concentration of 5000 µg/ml and antioxidant capacity of 2091 mg  ascorbic acid equivalent (AAE)/kg sample. The antioxidant activity of the optimum product by ferric reducing antioxidant power (FRAP) assay gave an antioxidant capacity of 2394 µmol AAE/kg sample. The optimum EPEP morphologically showed agglomerated particles.